Being a Woman in the Turkish Criminal Justice System - Hatıpoğlu-Aydın, Duygu (Women & criminal justice, 2021)
In Turkey, discrimination against women has cultural, sociological, and legal causes. Education, health, employment, and social life carry traces of gender discrimination. Gender inequality also occurs in the legal field. Especially in the criminal justice system, women experience disadvantages compared to men. Despite the gender-neutral laws, discrimination is widespread and affects law enforcement, which is dominated by patriarchal social codes and prejudices. This study aims to focus on women as victims and offenders in the Turkish criminal justice system, with examples and assessments from investigation of the corrections system.